Occupational changes related to the experience of anorexia and bulimia nervosa by adolescents: Scope review (Research, Society and Development, 2021)
Introduction: Eating disorders, specifically anorexia nervosa (AN) and bulimia nervosa (BN), mainly affect adolescents. The experience of these disorders can cause impacts and functional limitations in daily life. One of the focuses of Occupational Therapy is the analysis of factors that can influence the involvement of people in their occupations. Objective: To describe the occupational changes related to the experience of AN/BN by adolescents, discussed in scientific articles published in Brazilian magazines from 2009 to 2019. Method: Scope review whose data were collected on the VHL, VHL Adolec Brasil platforms and the SciELO database. The texts published in the period from 2009 to 2019 were included, which used the field research method, written in Portuguese and which reported impacts on the occupations of adolescents with AN/BN. Changes in occupations were categorized considering their different types, and presented in a descriptive manner. Results: The publications were from magazines from different professional areas; more often from authors of psychology and only one text from an occupational therapist; the main place of research was hospitals and the largest number of studies were with female participants only. The altered occupations were related to personal care, food, social relationships, physical activity, self-harm, studying and sleeping. Conclusion: The results obtained showed the occupational changes related to the experience of AN/BN by adolescents, as well as the importance of Occupational Therapy guidelines for this audience.